Interinstitutional collaboration for end-user bioinformatics training: Cytoscape as a case study. - Brandenburg, Marci D.; Garcia-Milian, Rolando (Journal of the Medical Library Association, 2017)
Background: This case study describes the value of and need for interinstitutional collaboration to train biomedical researchers in data visualization, using Cytoscape network analysis software as an example. To provide training on Cytoscape software to Yale University biomedical researchers, a collaboration was formed between the Yale Harvey Cushing/John Hay Whitney Medical Library's (CWML's) biomedical sciences research support librarian and the University of Michigan (U-M) Taubman Health Sciences Library's bioinformationist, who has expertise in Cytoscape software. Case Presentation: The U-M bioinformationist offered a webinar to the Yale community, followed by a one-day onsite workshop. This collaboration allowed Yale biomedical researchers and librarians to receive training on Cytoscape software, in addition to giving the Yale librarian a collaborator for answering future questions about the software. Conclusions: This collaboration furthered the U-M bioinformationist's role in the field as an expert in Cytoscape instruction, while also establishing the CWML as a leader in providing support for analyzing and visualizing molecular data at Yale University. The authors found this collaboration to be a successful way for librarians to fill end-user training gaps in rapidly changing fields such as bioinformatics.